Case reportEarly occlusion of the non-infarct-related coronary artery following successful primary percutaneous coronary intervention in ST-elevation myocardial infarction - Wolny, Rafał; Pręgowski, Jerzy; Bekta, Paweł; Chmielak, Zbigniew; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
We present a clinical case of early occlusion of the non-infarct-related artery (non-IRA) in a patient with ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI). Several hours after successful percutaneous treatment of the occluded right coronary artery the patient developed a second myocardial infarction, which was caused by acute occlusion of the left anterior descending artery, which had a significant lesion in the proximal segment. The lesion was diagnosed during the first catheterization, but was left untreated. We discuss the potential advantages and risks associated with the ad-hoc multivessel PCI strategy in STEMI